Bird inventory on Syiah Kuala University Darussalam, Banda Aceh, Indonesia - Aida Fithri (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The research of Bird inventory on Syiah Kuala University Darussalam Banda Aceh had been done by using direct observation method. As much as 26 bird species  that were  included in 19 families were found during 2006-2012.  Among these birds are three species of protected birds and two species of migratory bird.